1992
DOI: 10.1111/j.1570-7458.1992.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Rearing of two predators, Thanasimus dubius and Temnochila virescens, for the biological control of Ips grandicollis in Australia

Abstract: Rearing methods for two coleopterous predators, Thanasimus dubius and Temnochila virescens, imported into Australia for the biological control of Ips grandicollis, were developed. Bionomic data obtained from laboratory rearings between 1982–1987 showed that T. dubius eggs took about 7 days to hatch and that duration of the larval stage was about 42 days. Observations showed that T. dubius had a prolonged prepupal stage (x̄ = 56.4 days, range 14–274 days), which was probably non‐diapausal in nature. Mean adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
1
15
1
2
Order By: Relevance
“…Emergence generally occurred in several different episodes distributed across a 2-year period, with the bulk of the emergence in spring and autumn. The first emergence episode for a given tree roughly coincides with the development time found in laboratory studies at constant temperatures (Nebeker & F'urser, 1980;Lawson & Morgan, 1992). For those emerging after the first peak there are two likely explanations: (1) some individuals undergo a period of diapause (Tauber et&, 1986), probably as prepupae in their cells in the outer bark, or (2) some larvae take considerably longer to develop, perhaps due to a shortage of prey inside the tree.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Emergence generally occurred in several different episodes distributed across a 2-year period, with the bulk of the emergence in spring and autumn. The first emergence episode for a given tree roughly coincides with the development time found in laboratory studies at constant temperatures (Nebeker & F'urser, 1980;Lawson & Morgan, 1992). For those emerging after the first peak there are two likely explanations: (1) some individuals undergo a period of diapause (Tauber et&, 1986), probably as prepupae in their cells in the outer bark, or (2) some larvae take considerably longer to develop, perhaps due to a shortage of prey inside the tree.…”
Section: Discussionmentioning
confidence: 92%
“…A natural enemy with a long life cycle relative to D. frontalis, for example, would provide a simple explanation for the delayed density dependence in this system. Previous studies of T. dubius have examined its development in the laboratory at constant temperatures, where it displays a unimodal distribution of emergence times and a life cycle two or three times as long as D. frontalis (Mignot & Anderson, 1969;Nebeker & Purser, t980;Lawson & Morgan, 1992). However, a preliminary field study found a much more complex pattern of development, including several peaks of emergence, and some individuals emerging nearly 2years after D. frontalis attack (Reeve etal., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Hábitat y hábitos. La gran mayoría de los miembros que componen el género Enoclerus son depredadores de larvas y adultos de otros insectos tanto en estadios inmaduros como en la etapa adulta; generalmente son asociados a plantas herbáceas y arbustivas en zonas tropicales y subtropicales sobre las cuales se encuentran depredando una amplia gama de insectos (Mawdsley 2001), aunque un número limitado de ellos se encuentra fuertemente asociado a especies de coníferas en bosques de clima templado, alimentándose de una extensa variedad de escarabajos descortezadores, siendo importantes reguladores poblacionales de estos mismos (Bunt et al 1980;Dixon & Payne 1980;Lawson & Morgan 1992;Billings et al 1996;Reeve 1997;Opitz 2002;Reeve et al 2003;Bentz 2006;Domínguez-Sán-chez et al 2008;Hansen et al 2009). Estatus y clasificación.…”
Section: Resultsunclassified
“…Todos los especímenes involucrados fueron identificados por el primer autor. Las muestras fueron colectadas mediante el uso de trampas multiembudo tipo Lindgren (Lindgren 1983), utilizando la feromona frontalina (1,5-dimetil-6-8-dioxabiciclo[3.2.1] octano), cebando cada trampa con una proporción fija de fórmula sintética la cual consistió en una dosis de 400 µl de capacidad de baja densidad de microcentrífuga de polietileno conteniendo 300 µl de frontalina racémica (Chemtica Internacional, San José, Costa Rica) (Moreno et al 2008), con dosis universal para todos los sitios de muestreo por trampa; la frontalina es un acetato bicíclico producido de forma natural por varias especies del género Dendroctonus (Lawson & Morgan 1992;Billings et al 1996;Reeve 1997;Paine et al 1999;Barkawi et al 2003, ), se utilizaron otros atrayentes como señuelos los cuales fueron colocados junto con la dosis previamente señalada de la feromona frontalina específicamente de la siguiente forma: los ejemplares obtenidos en el estado de Chiapas fueron colectados a partir de octubre de 2003 hasta agosto del 2004, utilizando los siguientes tratamientos: 1) testigo (ausencia de feromona y otros atrayentes), 2) aguarrás y 3) frontalina. Las colectas en el estado de Michoacán fueron llevadas a cabo desde junio de 2005 hasta septiembre de 2006 con el atrayente químico frontalina, no se utilizó ningún tipo de combinación con otros atrayentes.…”
Section: Materials Y Métodosunclassified
“…Although few biological control programs have been successful in forestry (Berryman, 1967;Zondag, 1979;Lawson & Morgan, 1992;Fielding & Evans, 1997), several studies have explored the possibility of using natural predators as biocontrol agents of bark beetles (Coleoptera: Curculionidae: Scolytinae) (Berryman, 1967). Some authors suggest that the natural populations of predators might be manipulated by using semiochemicals (Aukema et al, 2000).…”
Section: Introductionmentioning
confidence: 99%